The violence of the masculine ideal: A case for nomadic masculinities - Siphiwe I. Dube (HTS Teologiese Studies/Theological Studies, 2018)
In this article, I argue that a different kind of discourse on Christian masculinities in post-apartheid South Africa is possible despite the prevalence of largely idealised and politically conservative ideologies of masculinities promoted primarily through the public and private performance of violent masculinities. Drawing on a redacted critique of current prevalent discourses of transformation in critical masculinities studies such as alternatives masculinities, hegemonic masculinities, liberated masculinities and toxic masculinities, I underscore how these discourses are limited in their thinking on masculinities in general as they presume the ideal of what a liberated man should be like. Specifically, I argue that idealised masculine ideals, even in their liberatory forms, eschew mobility and fluidity and, therefore, end up restricting the possibility for transformative action. I propose, instead, that we reinscribe discourses of Christian masculinities with the notion of nomadic subjectivity, espoused by Rosi Braidotti, as a form of transpositional praxis of being in order to expand our linguistic repertoire of transformative masculinities. Such a shift in focus, as I demonstrate, has the propensity to aid us in constructing and implementing creative and imaginative programmes of engaging men in rethinking scripts of masculinities.